PENERAPAN MODEL PROJECT BASED LEARNING LERBASIS APLIKASI TRACKER DALAM MENINGKATKAN HASIL BELAJAR PADA MATERI GERAK JATUH BEBAS - Entjaurau, Seplin; Bujung, Cyrke A N; Mondolang, Aswin; Makahinda, Tineke; Rende, Jeane; Tumimomor, Farly R (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to determine the effect of implementing the Tracker application-based Project Based Learning (PjBL) model on improving student learning outcomes in free fall motion material. This study is based on the lack of use of technology-based learning media in physics learning, as well as low student active involvement in the learning process. The method used is a quasi-experiment with a pretest-posttest control group design. The research subjects were 11th grade students at SMA Negeri 1 Tondano, consisting of two classes, namely the experimental class and the control class. The results showed a significant increase in student learning outcomes in the experimental class compared to the control class. The average post-test scores of students in the experimental class were higher than those in the control class. The use of the Tracker application was effective in helping students understand the concept of free fall motion through video and graphic analysis. Based on statistical tests (t-tests), a significance value of less than 0.05 was obtained, indicating that there was a significant difference in learning outcomes between the two classes.